Pemanfaatan Laboratorium IPA Dan Bahasa Pada Madrasah Aliyah Swasta - Umul Hidayati (Badan Litbang dan Diklat Kementerian Agama RI, 2013)
In an effort to increase the quality of education in Madrasah, the government (the Minister of Religious Affairs through Islamic Education General Director), since 1995, has performed a supportive program in science laboratories by providing for needs in several MTsN (Islamic public junior high schools). In the year 1998, support was given to 35 MAN (Islamic public senior high schools) and in the year 2005 to several considerably superior MA (Islamic private high schools). In the year 2010 support was given to 400 private MA in 19 provinces. In the same year, support was given to 100 MA laboratory facilities in 11 provinces. The massive amount of support has not yet been able to be used optimally in order to increase the quality of education by the Madrasah(s) because of many obstacles such as: the low quantity of human resources (teacher and laboratory staff), the fact that several MA do not possess a laboratory building (Science and Linguistic major), and the fact that science and linguistic majors do not exist in several Madrasah. On the other hand, distribution of funds also experienced many difficulties. The result of the research of the Center of Research and Development Islamic Education and Religion in the year 2012 entitled the â€œUse of the laboratory facilities in Madrasah (the study of the well-funded science and linguistic laboratory Madrasah Aliyah)â€ indicates that the use of laboratory facilities has not yet been maximized by the Madrasah and support for implementation has experienced many difficulties.Â Dalam upaya meningkatkan mutu pendidikan di Madrasah, pemerintah (Kementerian Agama melalui Dirjen Pendis) mengeluarkan program bantuan sarana laboratorium IPA yang dimulai tahun 1995 dengan memberikan bantuan pada beberapa MTsN. Pada tahun 1998, bantuan diberikan kepada 35 MAN dan pada tahun 2005 bantuan diberikan kepada beberapa MA Unggulan. Pada tahun 2010 bantuan diberikan kepada 400 MA swasta di 19 propinsi. Pada tahun yang sama, juga diberikan bantuan sarana laboratorium bahasa pada 100 MA swasta di 11 propinsi. Besarnya bantuan yang diberikan selama ini ternyata belum dapat dimanfaatkan madrasah secara maksimal untuk meningkatkan mutu pendidikan karena terkendala oleh banyak hal antara lain terbatasnya SDM (pendidik dan tenaga laboran), sebagian MA belum memiliki gedung laboratorium (IPA dan bahasa); tidak memiliki jurusan IPA dan bahasa. Di samping itu, dalam pelaksanaannya pemberian bantuan ini juga masih menuai banyak masalah.Hasil penelitian Puslitbang Pendidikan Agama dan Keagamaan tahun 2012 berjudul Pemanfaatan Sarana Laboratorium Pada Pendidikan di Madrasah (Studi Pada Madrasah Aliyah Penerima Bantuan Laboratorium IPA dan Bahasa)â€menunjukkan bahwapemanfaatan sarana laboratorium oleh madrasah belum maksimal dan pemberian bantuan tersebut dalam pelaksanaannya banyak menuai masalah.